A protocol for loading Calcein-AM into extracellular vesicles from mammalian cells for clear visualization with a fluorescence microscope coupled to a deconvolution system. - María-Angélica Calderón-Peláez; Jaime E Castellanos; Myriam L Velandia-Romero (PLoS ONE)
Extracellular vesicles (EVs) are membrane-bound structures produced and released into the extracellular space by all types of cells. Due to their characteristics, EVs play crucial roles in cellular communication and signaling, holding an immense potential as biomarkers and molecular transporters. Various methods have been developed to label and characterize EVs, however, visualizing EVs remains a process that requires highly specialized and expensive equipment, which is not always available in all the laboratories. In this study, we adapted a protocol originally designed for EVs analysis by flow cytometry using Calcein-AM, and convert it into a useful and effective tool for visualizing EVs by epifluorescence microscopy coupled with a deconvolution system. This approach can be very useful for basic EVs analyses, enabling researchers to verify their distribution and internalization across cells. Such insights can guide decisions on whether to advance to more detailed analysis using confocal microscopy or to perform additional assays.